Factors Related to Dental Health Service Utilization in Makassar City, Indonesia - Triana Amaliah Jayanti; Abdullah, Muhammad Tahir; Muchlis, Nurmiati; Ahri, Reza Aril; Samsualam, Samsualam; Andi Rizki Amelia (Postgraduate Program in Public Health, Universitas Muslim Indonesia, 2021)
Background: The awareness on dental hygiene among Indonesian is still low. As a result, very limited citizen who visit the dentalcare. Aim: The purpose of this study is to analyze the relationship between behavior determinants with dental health services utilization at Kapasa Health Center. Method: This type of research is analytic observational with a quantitative approach, with a cross sectional approach. The samples were 96 respondents from the community in the working area of ​​Kapasa Health Center. The data were analyzed using chi-square and logistic regression test. Results: The results showed the low utilization of dental health services at Kapasa Health Center (26.0%). The results of the relationship analysis showed that there were relationship between knowledge (p=0.020), perception (p=0,001), attitude (p=0.016), education level (p=0.010), health insurance ownership (p=0,022), family support (p=0.043) with dental health services utilization. There were no relationship between health information (p=0.109), health facilities (p=0.051), health workers support (p=0.435) with dental health services utilization at Kapasa Health Center. Conclusion: The health insurance ownership is the most dominant in the utilization of dental health services at Kapasa Health Center with a value of B is +2.881. The value of B is positive, meaning that if you have health insurance, it will increase the utilization of dental health services at Kapasa Health Center. The value of Exp (B) is 17.835 which means that having health insurance will result in peoples utilize dental health services at public health center which is 17.835 times greater than if does not have health insurance.